Customer satisfaction with online platform: A case study on Shopee Malaysia - Jamaludin, Jeniza; Abdul Rahman, Normy Rafida; Mohamad, Nur Izzaty; Aedah, Abd Rahman; Cging, Kow Wei
The rapid growth of e-commerce has significantly impacted the retail industry, with online platforms becoming increasingly popular among consumers. Shopee was Southeast Asia's largest e-commerce site. It is presently one of the most prominent e-commerce websites in Malaysia. Shopee has rapidly expanded across Southeast Asia in recent years, despite staff competition in the online retail sector. Its quick expansion is due to its substantial competitive advantages. This research project aims to assess the level of customer satisfaction with the online platform Shopee Malaysia. The goal of this study is to look at the most critical factors that impact Shopee customer happiness. The major goal of this research is to find out what factors influence customer satisfaction among Shopee customers in Malaysia. A quantitative method approach will be adopted, incorporating both quantitative surveys and qualitative interviews to gather comprehensive data. The findings of this research will provide valuable insights for e-commerce businesses, enabling them to improve customer satisfaction and loyalty on their online platforms.40 selected Shopee customers in Malaysia were sent a set of selfadministered questions. The three independent variables of convenience, cost, and availability were evaluated in connection to the dependent variable of consumer satisfaction with Shopee, a Malaysian online shopping platform. Finally, this research contributes to a deeper understanding of Shopee's online buying services in Malaysia that influence customer satisfaction and explore strategies to enhance the overall shopping experience on the platform.